Physical Modeling of Rainfall and Induced Landslide (International Journal of Innovative Research in Engineering & Management, 2022)
Rainfall and Snowfall induced landslides  are one of the most common and damaging natural hazards  on Jammu and Kashmir region that not only degrade land in  hilly areas but additionally causing deaths and destruction  on natural slopes and cause tremendous losses. These slope  failures usually influence by rain intensities which vary with  time that is extremely common in Jammu Kashmir highway.  The intensity and time duration of rainfall over a catchment  area decide the property and magnitude of the landslide  occurred by the rainfall. Deep slope failure mostly occurred  by long duration rain over a catchment area, whereas  shallow failure is related to very short-term rain with high  intensity. The study shows that slope geometry and rainfall  intensity are the major affecting parameter which generally  cause landslide by the action of depletion of water through  the soil pores which leads to the development of lubrication  effects between soil particles and hence reduction in shear  strength parameter of soil particles. It also indicates that  permeability and density of the soil also playing an  important role in slope failure mechanism.
Keywords: Rainfall; Snowfall; Landslide; Destruction; Failure; Catchment area